PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI MELALUI KOMPETENSI PEGAWAI SEBAGAI VARIABEL INTERVENING - Awan Anhara; Wawan Prahiawan; Suherna Suherna (Niagawan, 2023)
The purpose of this study was to examine the influence of transformational leadership and the use of information technology, serving, and employee relations for improving employee performance. This research was conducted at the Office of the Investment and One-Stop Services Office of DPMPTSP, Serang City, Banten Province. This research used an explanatory survey method approach, where data was taken from a sample of the population in order to obtain the explanation and relationship between the variables. This method was used to explain the relationship between transformational leadership and the use of information technology on performance through competence which was explained using hypothesis testing, qualitative and causality. This study used a saturated sample to take the total population to be used as a sample for total population of 88 people. Data analysis was carried out by testing the measurement model, testing the structural model and testing the indirect effect. The results of this study found that several hypotheses were accepted: (1) the effect of transformational leadership (x1) on employee performance (y) was significant and the value 0.326, (2) the effect of information technology utilization (x2) on employee competence (z) with a significant value of 0.488, and (3) the effect of using information technology (x2) on employee performance (y) was significant with a value of 0.407. While the hypothesis was rejected, namely: (1) there is no effect of transformational leadership (x1) on employee competency (z) was significant with a value of 0.285 and (2) there was no significant effect of employee competence (z) on employee performance with a value of 0.080.